2014
DOI: 10.18388/abp.2014_1916
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for sonication-assisted Agrobacterium rhizogenes-mediated transformation of haploid and diploid sugar beet (Beta vulgaris L.) explants.

Abstract: Hairy root cultures obtained after Agrobacterium rhizogenes-mediated genetic transformation can serve as a model system for studying plant metabolism and physiology, or can be utilized for the production of secondary metabolites. So far no efficient protocol of hairy root development in sugar beet has been publically released. In this work, two A. rhizogenes strains (A4T and LBA1334) carrying a binary vector pBIN-m-gfp5-ER or pCAMBIA1301 possessing gfp and uidA reporter genes were used to transform petiole exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Moreover, micro wounding of cells enables secretion of phenolic compounds enhancing agroinfection (Pathak, Hamzah, 2008). It was also demonstrated that short ultrasound treatment is the most efficient when applied to explants already immersed in the inoculum (Klimek-Chodacka, Baranski, 2014). We therefore compared three sonication times and have shown that SAAT stimulates hairy root induction independent on the explant type and bacteria strain used.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, micro wounding of cells enables secretion of phenolic compounds enhancing agroinfection (Pathak, Hamzah, 2008). It was also demonstrated that short ultrasound treatment is the most efficient when applied to explants already immersed in the inoculum (Klimek-Chodacka, Baranski, 2014). We therefore compared three sonication times and have shown that SAAT stimulates hairy root induction independent on the explant type and bacteria strain used.…”
Section: Discussionmentioning
confidence: 96%
“…Histochemical localization of GUS activity in hairy roots was performed using the 5-bromo-4-chloro-3-indolyl glucuronide (x-Gluc) (Duchefa Biochemie, Haarlem, The Netherlands) substrate essentially according to Jefferson et al (1987) and described in details before (Klimek-Chodacka, Baranski, 2014). Then hairy root pieces were rinsed in 70% ethanol for 5 min and GUS activity was scored based on tissue blue staining.…”
Section: Gus Histochemical Stainingmentioning
confidence: 99%
“…Being a very easy method, of low cost, and significant to enhance Agrobacterium-mediated gene transfer are the benefits of SAAT method. Apart from successful application of SAAT in the transformation of Chenopodium rubrum L. [78] and Beta vulgaris L. [79], this approach has also been applied in the production of recombinant Escherichia coli wild-type heat-labile holotoxin and Escherichia coli mutant LT vaccine adjuvants in Nicotiana tabacum, in which the highest systemic LT-B-specific IgG titres were detected in birds [80]. Recently, another approach called the combination of sonication plus vacuum infiltration assisted Agrobacteriummediated transformation had evolved to optimise the efficiency of Agrobacterium-mediated gene transfer [76].…”
Section: Sonication Sonication Is a Technique That Utilizes Soundmentioning
confidence: 99%